2008
DOI: 10.1111/j.1747-0285.2008.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Lipophilic Hydroxyurea Derivatives: Synthesis, Cytostatic and Antiviral Activity Evaluations

Abstract: The novel hydroxyurea derivatives of l- and d-amino acid amides 5a-l were prepared by aminolysis of N-(1-benzotriazolecarbonyl)-amino acid amides 4a-f with O-benzylhydroxylamine and N-methylhydroxylamine and evaluated for their antiviral and cytostatic activity against malignant tumor cell lines and normal human fibroblasts. Compounds 5a, 5c, 5e and 5k showed the highest antiproliferative effects against all tumor cell lines tested. The strongest non-specific cytostatic activities against HeLa cells were affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 6 publications
4
11
0
Order By: Relevance
“…We have previously shown that BOU and MHCU exerted the strongest antiproliferative effect upon a panel of tested cell lines, including the metastatic colon cancer cell line SW620 [6,7]. Tested compounds are both amino acid derivatives of HU, with the same amide moiety and a different amino acid part: BOU is a d -phenylglycine and MHCU is a l -phenylalanine derivative.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that BOU and MHCU exerted the strongest antiproliferative effect upon a panel of tested cell lines, including the metastatic colon cancer cell line SW620 [6,7]. Tested compounds are both amino acid derivatives of HU, with the same amide moiety and a different amino acid part: BOU is a d -phenylglycine and MHCU is a l -phenylalanine derivative.…”
Section: Resultsmentioning
confidence: 99%
“…These processes are connected to down-regulation of colorectal cancer malignancy biomarkers TAGLN2 and Gal-3 [21,22] as well as the metastatic phenotype marker PAI-RBP1 [23]. In conclusion, down-regulation of specific CRC proteins involved in tumor progression and invasion might explain the selective activity of BOU on the metastatic SW620 cell line in comparison with other tested tumor cell lines derived from solid tumors [6]. Moreover, it seems that cell death mechanisms might be triggered by metabolic changes and oxidative stress through activation of caspase 7 and down-regulation of two crucial oxidative stress-protecting proteins, DJ-1 and PRDX3, in treated SW620 cells (Table S2 in Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Benzotriazole moiety in compounds 27 was readily replaced with amines or hydroxylamines affording ureidoamides 29 and hydroxyureidoamides 30. [24][25][26] Ureidoamides 31 were prepared directly from chlorides 25 with excess of 2-aminoethanol, 3-aminopropanol and 5-aminopentanol. 27 On the other hand, amidation of chlorides 25 with N-phenylhydroxylamine gave hydroxamic acids 33, which readily cyclized to oxadiazines 34 (Scheme 4).…”
mentioning
confidence: 99%